2010
DOI: 10.1007/s11947-010-0374-9
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Proteases in Pacific Whiting (Merluccius productus) Muscle as A Processing Aid in Functional Fish Protein Hydrolysate Production

Abstract: A fish protein hydrolysate (FPH) from Pacific whiting (Merluccius productus) muscle was produced by autolysis of a minced homogenate (8% protein) at pH 7.0 and 60°C, where maximum endogenous proteolytic activity was detected. FPH production was controlled by the pH stat method, yielding a 4.43% degree of hydrolysis after 1 h of autolysis. Upon autolytic processing, 28.9±0.7% of the total protein was found in the soluble fraction. FPH was 100% soluble at pH 7.0 and 10.0 and was less soluble at pH 4 (82.5%, P ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 36 publications
(53 reference statements)
0
5
0
1
Order By: Relevance
“…EAI values obtained in this study were higher than the value of Chalamaiah et al (2010Chalamaiah et al ( , 2015a for hydrolysate of Cirrhinus mrigala and carp roe. A higher EAI indicates higher emulsion turbidity, thus representing a higher interfacial area in the o/w emulsion (Mazorra-Manzano et al, 2012). At a concentration of 0.5 mg mL À1 , both hydrolysates showed high ESI than other concentrations (313.75 min for pepsin and 235.97 min for Alcalase).…”
Section: Functional Propertiesmentioning
confidence: 98%
“…EAI values obtained in this study were higher than the value of Chalamaiah et al (2010Chalamaiah et al ( , 2015a for hydrolysate of Cirrhinus mrigala and carp roe. A higher EAI indicates higher emulsion turbidity, thus representing a higher interfacial area in the o/w emulsion (Mazorra-Manzano et al, 2012). At a concentration of 0.5 mg mL À1 , both hydrolysates showed high ESI than other concentrations (313.75 min for pepsin and 235.97 min for Alcalase).…”
Section: Functional Propertiesmentioning
confidence: 98%
“…La composición proximal de los hidrolizados proteicos de pescado (tabla 1) es importante en la perspectiva de la nutrición y salud del ser humano. Varios trabajos de investigación informaron que el contenido de proteína de los hidrolizados de proteína de pescado variaba entre 60% y 90% de la composición total (DONG et al, 2005;KHANTAPHANT;GHOMI, 2011;MAZORRA-MANZANO et al, 2012;OVISSIPOUR et al, 2009;PACHECO-AGUILAR;SOUISSI et al, 2007;THIANSILAKUL;SHAHIDI, 2007). Estos valores concuerdan con los hallados en los hidrolizados elaborados en este trabajo, donde se observó un contenido proteico de alrededor del 80% (Tabla 1).…”
Section: Resultados Y Discusiónunclassified
“…Previous studies also demonstrated that protein hydrolysates from various seafood sources contain moisture below 10% (Chalamaiah et al, 2010;Foh et al, 2011;Parvathy et al, 2016) which facilitates better handling as well as storage stability. The ash content of the protein hydrolysate was 2.42±0.08% indicating a lower value in comparison to the range viz., 0.45 to 27% previously reported (Yin et al, 2010;Mazorra-Manzano et al, 2012).…”
Section: Proximate Compositionmentioning
confidence: 88%